Le climat et la ville : la nécessité d’une recherche croisant les disciplines - Morgane Colombert; Jean-Luc Salagnac; Denis Morand; Youssef Diab (VertigO)
With the observation of the urban climate and after the modeling of the physical phenomena, the climatologists are and were able to describe and to understand with more and more precision the formation of the urban climate. The first works were above all dedicated to the urban heat island observed globally on all the urban area. The climatologists were gradually interested in the other climatic parameters (pluviometry, wind, etc.) and in lower scales than the city, highlighting the importance of the urban geometry and the building materials. The urban climatology is a research thematic investigated at the same time by the climatologists and the geographers, but also by the architects and the town planners. This allows to set up a multidisciplinary approach and to integrate into the practice of the urban planning and the architecture some elements of urban climatology. So climatologists, geographers, town planners and architects could reflect together on the interest to take into account the urban climate in the urban planning and the architecture. We need some tools allowing to take into account the urban climate in the urban conception but priory has to be given to promote and to organize a better synergy between the various actions led in favour of the environment. Green infrastructures are a good example. Initially implemented to provide connexions between natural habitats of species by corridors, they can also improve the climatic quality of spaces.